The Newest Federalism and Population Health - JENNIFER KARAS MONTEZ; JACOB M. GRUMBACH (The Milbank Quarterly, 2026)
Policy Points In the United States, social policies at the federal, state, and local levels affect population health. The country is undergoing major changes in its social policies and intergovernmental relations. As both state and local governments have taken different approaches to social policies, where one resides and the socioeconomic resources one has increasingly have life and death consequences. The following three contemporary changes in intergovernmental relations may have profound consequences for population health: erosion of the federal floor, formation of cross‐state alliances, and circumvention of congressional policymaking. Context American federalism involves decentralized policymaking across federal, state, and local governments. Since the 1980s, changes in those intergovernmental relations, termed “New Federalism,” combined with polarization in policies across state and local governments, resulted in some places being conducive to health while others are not. This Perspective proposes that the country has entered “Newest Federalism” with contemporary changes in intergovernmental relations that carry profound, and largely unstudied, implications for population health. Method Drawing on the federalism, health policy, and population health literatures, this Perspective links New Federalism and state policy polarization to the troubling trends and growing disparities in population health since the 1980s. It then identifies three features of the current context, coined the Newest Federalism, that will adversely impact population health. Findings Three characteristics of the Newest Federalism are particularly important. These include the erosion of the federal floor, evident in the declining real minimum wage, repeal of federal abortion protections, cuts to SNAP and Medicaid, threats to the Department of Education, and more; formation of cross‐state alliances that fill federal policy vacuums in areas such as public health, data privacy, and reproductive rights, but that may themselves widen disparities between states; and growing use of executive orders, agency actions, and waivers to circumvent congressional policymaking. These changes may harm population health overall and disproportionately affect people with limited socioeconomic resources and those living in states that cannot or will not offset federal retrenchment. Conclusions Understanding and mitigating the health consequences of the Newest Federalism will require research that examines the combined effects of federal, state, and local policy change, attends to the distributive consequences of cross‐state alliances, and informs policymakers and the public about the stakes for population health.